파이썬을 이용한 사용자 중심의 적응적 영문 타이핑 프로그램 구현 - 김희숙(Hye-Suk Kim); 이호준(Ho-Jun Lee); 탁동길(Dong-Kil Tak) (디지털콘텐츠학회논문지, 2018)
본 논문에서는 영어를 PC상에서 효과적으로 타이핑하면서 영어 학습 효과까지 얻기 위하여 파이썬의 클래스와 함수 구조를 이용하여 사용자 중심의 적응적 영문 타이핑 프로그램을 구현한다. 사용자는 필요한 영어 예문을 텍스트 파일로 생성한 후 연결하여 영문 타이핑 연습에 활용할 수 있도록 하고 타이핑 연습에 사용된 영어 문장을 기반으로 기억력 테스트를 할 수 있는 기능을 제공하여 영어 학습 효과를 얻을 수 있도록 한다. 구현된 프로그램의 인터페이스는 게임 형식으로 구성하여 흥미롭게 접근할 수 있고 사용자간의 순위를 공개하여 타이핑 속도와 영어 학습에 긍정적인 자극을 제공하여 사용자들의 영문 타이핑 속도를 향상시킴과 동시에 영어 학습 효과까지 높일 수 있을 것으로 기대한다. In this paper, we implemented a user - oriented adaptive English typing program using class and function structure provided by Python to get English learning effect while effectively typing English on PC. The user of the implemented English typing program creates a text file of required English example sentences and links them to use it for direct English typing exercise. In addition, based on the English sentence used in the English typing exercise, it is possible to obtain the English learning effect by providing the ability to perform the memorization test. The interface of the program is structured in the form of a game so that it can be accessed interestingly, and the ranking among the users is disclosed to provide a positive function. We expect that the implemented program will improve the user 's English typing speed and improve the English learning effect. KCI Citation Count: 2